Metode Vector Error Correction Model (VECM) dalam Menganalisis Hubungan Kurs Mata Uang Terhadap Ekspor Di Indonesia - Nate, Iko Penantu; Endraswati, Hikmah (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
In the era of increasingly rapid digitalization, the application of information technology has become an urgent need for various sectors, including the economic and business sectors. However, technology acceptance is not always easy because there are various factors that influence adoption by users. To understand these factors, a theoretical approach is needed that can effectively predict technology acceptance. One model that is often used for this purpose is the Technology Acceptance Model (TAM), which focuses on how perceived usefulness and perceived ease of use affect user intentions to accept new technology. Based on this background, this study aims to identify and analyze the impact of the exchange rate on Indonesian exports. The data used in this study are monthly exchange rate and export data from January 2017 to December 2021. The stationarity test uses the Augmented Dickey-Fuller (ADF) method and differentiation is used to ensure stationary data. The optimal delay length is determined based on the Akaike information criterion (AIC). The Vector Error Correction Model (VECM) is estimated after determining the optimal delay length. Granger causality test is used to determine the reciprocal influence between variables, while impulse response function (IRF) is used to track the impact of variable shocks. The results of the analysis show that there is a significant relationship between exchange rates affecting exports, while exports do not affect the exchange rate.